The Computational Calculation and Molecular Docking of Aeroplysinin-1 As Antibacterial - Maahury, Mirella Fonda; Allo, Veliyana Londong (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2021)
Aeroplysinin-1 is naturally found from marine sponges as an anti-bacterial compound. Computational calculation and molecular docking were performed for aeroplysinin. Aeroplysinin as an inhibitor has optimized in the gas phase using DFT with 6-31G(d) functional. The structure from geometry optimization of aeroplysinin-1is, not in one plane. The interaction of aeroplysinin-1 with two different DNA gyrase from E. Coli and S. Aureus. In this research,aeroplysinin-1 can inhibit the protein with the free binding energy of about -5.7 kcal/mol and -6.35 kcal/mol, respectively, for E. Coli and S. Aureus. The dominant molecular interaction is the hydrogen bond.